Innovative Learning Strategies in Teaching Verses of Thaharah - Wiseno, Sekar Galuh Putri; Nurrohim, Ahmad; Fitria, Salwa Aida; Iqbal, Achmad Ichsanul Alaudin; Fauzi, Ahmad Akbar; Burhanudin, Mohammad Siyam; Fauzan, Ahmad (Universitas Muhammadiyah Surakarta, 2023)
Learning at school requires improvement or renewal so that the learning process becomes more interesting and not monotonous, because students need a comfortable learning atmosphere so that they can easily understand the material delivered by the teacher through existing learning conversations. With this innovative learning strategy, the learning atmosphere becomes more pleasant and can increase student learning motivation. This article explains and provides an overview of innovative learning strategies for Tharaha learning materials. These innovative learnings include Unclean, Hadast (major, medium, small) and the ordinances of ablution, tayammum and compulsory bathing. Thaharah learning with innovative learning strategies through games, videos and exercises that help students better understand what is being learned and can increase interest in learning. The purpose of this innovative learning method is for students to feel comfortable and happy in learning, but not neglecting the most important learning material that can be learned in everyday life and practiced. Another goal of this innovative strategy is as a learning reform aimed at attracting students' attention.